Collective action and collaborative management of forests - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Governments around the world increasingly seek to manage their forests with the collaboration of the people living nearby. Forestry Ministries or their equivalents usually do this by offering local people access to selected forest products or forest land, income from forest resources, or opportunities for communicating with government forestry officials. In return, the agency obliges local people to cooperate in managing the forests around them by protecting existing forest or by planting trees.